The EFEKTIVITAS METODE TIGA SATU TIGA KATEKESE DARING AKAR RUMPUT PADA MASA PANDEMI COVID-19 - Kanisius Dadi (Unika Santu Paulus Ruteng, 2021)
Covid-19 pandemic conditioned people to implement social distancing in each social activity. This condition impacted the process of catechesis. This research aims to analyze the effectiveness of three one three online catechesis processes in keeping the essence of catechesis during the Covid-19 pandemic situation in grass root level. The facilitator of catechesis performed planning, implementation, and evaluation of the online catechesis using gadgets and the internet. Since the early 1980s, faith dan spiritual developers used computers and the internet to promote faith and spiritual development. The catechesis facilitator implemented